SKILLS OF THE ENGLISH LANGUAGE TEACHER AS A SECOND LANGUAGE IN THE POST-PANDEMIC CONTEXT IN PUBLIC SCHOOLS - Souza, Manuela Xavier Ribeiro de; Coutinho, Diógenes José Gusmão (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2025)
Abstract: This study investigates the challenges faced in English teaching during the Covid-19 pandemic, addressing the difficulties and strategies adopted by educators and students during this period. The research was conducted through a review of existing literature, utilizing original articles found in relevant databases. The results indicate that the lack of technological infrastructure and limitations in teacher training were the main obstacles, compromising student engagement and the effectiveness of pedagogical practices. Furthermore, the analysis emphasizes the need for new approaches and the importance of investments in technology and ongoing training for educators. It is concluded that to ensure quality English teaching, it is essential to promote methodological adaptations that meet the demands of the contemporary educational environment.